THE DEMOGRAPHIC DROP IN THE MOLISE REGION. FROM 1861 TO 2011, WITH A LOOK TO THE FUTURE - Cristiano Pesaresi (Bollettino della Società Geografica Italiana, 2019)
During the century between the 1870s and the twentieth century emigration flows strongly conditioned the history of Molise, even representing a peculiar and distinctive element. Over these hundred years, the triggering factors and causes, the destinations chosen and many other aspects deeply changed with regard to the figure of the migrant, but the process that came about was ‘charged’ with people to such an extent with their hopes and traditions, fears and nostalgia, their anger and desire for improvement, that it is possible to speak of an exodus that drained great part of the region. At present the migration balance shows positive values, with immigration from abroad beginning to acquire some significance, but the legacies of the past, which considerably altered the demographic structure, continue to produce effects on the natural balance. The main purpose of this paper is to give synthetic crosssections on the long and short term dynamics and demographic variations, focussing the attention on the 2001-2011 decade and the possible future trends, after referring to emigration flows that in certain decades, above all in 1951-1971, undermined the pyramid of the population. Finally, the migration balance of the last decade will be examined which, on the other hand, makes it possible to curb the decreases which would otherwise acquire greater values. By applying various levels of detail and from a diachronic and distribution point of view, the objective is to give an overall picture that might highlight some of the important evolutionary events and territorial aspects, aimed at a reflection on the possible scenarios and the demographic components to be rectified in order to avoid the haemorrhage taking place from spreading to the whole region.